Liberté, Égalité, Crédibilité: An experimental study of citizens' perceptions of government responses to COVID‐19 in eight countries. (5th January 2023) - Amirkhanyan, Anna A.; Meier, Kenneth J.; Song, Miyeon; Roberts, Fei W.; Park, Joohyung; Vogel, Dominik; Bellé, Nicola; Molina, Angel Luis; Guul, Thorbjørn Sejr
Abstract: During a global pandemic, individual views of government can be linked to citizens' trust and cooperation with government and their propensity to resist state policies or to take action that influences the course of a pandemic. This article explores citizens' assessments of government responses to COVID‐19 as a function of policy substance (restrictions on civil liberties), information about performance, and socioeconomic inequity in outcomes. We conducted a survey experiment and analyzed data on over 7000 respondents from eight democratic countries. We find that across countries, citizens are less favorable toward COVID‐19 policies that are more restrictive of civil liberties. Additionally, citizens' views of government performance are significantly influenced by objective performance information from reputable sources and information on the disproportionate impacts of COVID‐19 on low‐income groups. This study reinforces the importance of policy design and outcomes and the consideration of multiple public values in the implementation of public policies.